DUKUNGAN KELUARGA DAN KEJADIAN STUNTED PADA ANAK BALITA DI KABUPATEN SIMEULUE - , Anita, Prof. dr. Djauhar Ismail, SpA(K), MPH, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Chronic malnutrition with stunting constitutes the most considerable global health threat for the child survival, particularly for children under-five. The prevalence of stunted children cases in Simeulue District, Aceh Province, still exceeds the national prevalence in which the district prevalence has reached 63.9%. The prevalence of malnutrition in Aceh is attributed to inadequacy of parental care in the feeding practice for the children. Objective: To find out the correlation of familyâs supports and the stunted children prevalence among under-five children. Method: This was an observational study using quantitative approach with cross-sectional design and supported by qualitative data was conducted. Subjects were 156 under-five children aged 24-59 months. Sample taking used three stage sampling method. The dependent variable was stunted under-five children, the independent variable was familyâs supports and the extraneous variables were familyâs structure, number of children, and maternal occupation. Prior the use of the questionnaire, validity and reliability tests were done. Data processing used univariable analysis, bivariable analysis with chi-square test, and multivariable analysis with logistic regression. . Result: Prevalence of stunting in Simeulue Regency was 57,05%. Multivariable analysis showed that there was a significant correlation between children without familyâs support with a value (OR=2,9